2022
DOI: 10.5812/jjnpp-128060
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Antioxidant, Antifungal, Antibacterial, and Anti-inflammatory Effects of Teucrium polium on Common Pathogens in Vaginitis: A Review

Abstract: Context: Pathological vaginal discharges are one of the most common reasons for referring to gynecological clinics. The use of herbal medicines has been considered as an effective and low-complication treatment method in recent years. In this study, we introduce Teucrium polium according to traditional Persian medicine and modern medicine’s point of view to investigate the antifungal, antibacterial, and anti-inflammatory effects of T. polium on common pathogens in vaginitis. Evidence Acquisition: This study is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…These obtained data revealed that A. halimus , H. tuberculatum , T. polium and P. equisetiforme extracts were the most efficient natural antibacterial against tested bacteria. Which agree with studies proven by Morad et al., [28,38] Al‐Saeghi et al., [28] Bardsiri et al., [39] and Ghazal et al [40] …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…These obtained data revealed that A. halimus , H. tuberculatum , T. polium and P. equisetiforme extracts were the most efficient natural antibacterial against tested bacteria. Which agree with studies proven by Morad et al., [28,38] Al‐Saeghi et al., [28] Bardsiri et al., [39] and Ghazal et al [40] …”
Section: Resultssupporting
confidence: 90%
“…These obtained data revealed that A. halimus, H. tuberculatum, T. polium and P. equisetiforme extracts were the most efficient natural antibacterial against tested bacteria. Which agree with studies proven by Morad et al, [28,38] Al-Saeghi et al, [28] Bardsiri et al, [39] and Ghazal et al [40] Due to their important content on phenolic compounds (flavonoids, terpenoids, phenolic acids…), plant extract are candidates to be natural efficient antibiotics according to Abdelhakim et al, [41] who revealed that these bioactive com- pounds exert several mechanisms of action at different levels; as molecular (inhibition the synthesis of DNA and proteins), structural (increasing membrane permeability) even cellular levels (decreasing membrane integrity, blocking oxidative respiration). However, the lowest activity was showed for both P. equisetiforme decocted extract and M. arvensis ultrasonic extract.…”
Section: Antibacterial Assaysupporting
confidence: 92%
“…1 This condition is caused by changes in the normal flora in the vagina. 2 The three most common vaginal infections are fungus, bacteria, and Trichomonas vaginitis. 3 Meanwhile, the three most common causes (70% of cases) are Trichomonas, bacterial vaginosis, and vulvovaginal candidiasis.…”
Section: Introductionmentioning
confidence: 99%
“…5 Symptoms of vaginitis are foul-odor discharge, dysuria, itching, inflammation of the external genitalia, dyspareunia and irritation or burning sensation. 2,4,6 Almost all women have experienced it at least one time during their lifetime, making this condition a common complaint of women worldwide and this gynecological diagnosis frequently found in the primary health services. [6][7][8] Vaginal infections can cause high stress, dissatisfaction with life, depression, low self-esteem, and decreased sexual activity as well as infertility.…”
Section: Introductionmentioning
confidence: 99%